rmc 2022
DOI: 10.46632/rmc/3/1/5
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study On Effectiveness of E-Learning Over Conventional Class Room Learning – A Case Study with Respect to Online Degree Programmes in Higher Education

Abstract: Learning and teaching domains is going on major higher education companies of e-learning Ideas and practices changes due to quick acceptance. Many universities all over the world are now begins to offer Internet based courses that complement classroom-based courses. Online courses offer learners various such as benefits facilities, Teachers and other close to students to serve flexibility and opportunities from various schools or around the world. The education system and mode of education is changing over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…However, students' learning was reported to be identical both ways, and students were satisfied with both methods [24]. Pallavi et al (2022) declared that more than 50% of the respondents feel online learning is as effective as conventional classroom learning [25]. In an e-learning environment that emphasizes learner-centered activity and system interactivity, remote learners can outperform traditional classroom students [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, students' learning was reported to be identical both ways, and students were satisfied with both methods [24]. Pallavi et al (2022) declared that more than 50% of the respondents feel online learning is as effective as conventional classroom learning [25]. In an e-learning environment that emphasizes learner-centered activity and system interactivity, remote learners can outperform traditional classroom students [26].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have shown the benefits of using the Flipped Classroom model in increasing student achievement (Pallavi et al, 2022). Previous study concluded that e-learning with the flipped classroom model is very helpful in introducing Information Technology and as an e-learning guide in other subjects (Rahmelina et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars defined school support under the particular research background of “school shooting” as sustainable efforts by schools to support traumatized youth (Strøm et al, 2016 ). With the continuous change and development of new technologies and knowledge systems (Nica, 2018 ), especially since the outbreak of COVID-19, a large number of studies pointed out that school teaching methods need to be continuously integrated with technology (Erfayliana et al, 2022 ; Khasawneh, 2022 ; Pallavi et al, 2022 ; Warden et al, 2022 ). At the same time, the concept of school support should also be constantly broadened and deepened.…”
Section: Discussionmentioning
confidence: 99%